Pelaksanaan Program Pengendalian Penduduk Di Dinas Pengendalian Penduduk Dan Keluarga Berencana Kota Bitung - Naungmapia, Stefny; Pioh, Novie R.; Londa, Very Y. (AGRI-SOSIOEKONOMI, 2023)
This research aims to explain and analyze the implementation of the family planning program at the Population Control and Family Planning Office of Bitung City based on the scientific research process on the science of development resource management. The research was conducted from March to April 2023. This research took place at the Population Control and Family Planning Office of Bitung City. The results showed that the human resources of program implementers were divided into three groups of work units, namely employees at the Bitung City Population Control and Family Planning Office, employees at the District UPTD. Cadres and PPKBD at the kelurahan level. Employees at the Population Control and Family Planning Office of Bitung City have responsibilities in implementing the program in accordance with their main tasks and functions in the field of population control, counseling and mobilization. Employees at the sub-district UPTD in implementing the program conduct counseling, family planning services and family data collection. Cadres and PPKBD at the village level in implementing the program function to increase family planning participation, reduce alocon dropout, reduce stunting rates, help facilitate family planning services, counseling and family assistance and report regularly every month.